A comparative study on accountancy practical students during Covid-19 pandemic: Malaysia and Indonesia experience / Nor Aishah Mohd Ali … [et al.] - Mohd Ali, Nor Aishah; Ab. Majid, Rozaiha; Abdullah, Salina; Mediawati, Elis; Widaningsih, Mimin (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This paper intends to explore the challenges confronted by the accounting students who have to undergo their practical training during Covid-19 pandemic between the two neighbouring countries, Malaysia and Indonesia. Survey was distributed to practical training Accountancy students from both local Malaysian university as well as in Indonesia. A total of 131 and 92 students respectively from Malaysia and Indonesia responded to the survey. the findings indicate that there is a huge difference the way in which students from two universities conducted their practical training during the pandemic period of Covid-19. Whilst the Malaysian continued with the practical training exercise through the discretion of the respective companies where the practical training took place by way of working from home. The Indonesian students were however, given assignment as replacement to the practical training which they have to foregone due to the pandemic. This study only consider the interns of Accountancy students within a local university from both countries. Other universities from the same countries may deal with the pandemic condition differently. This study provides important information for decision makers involved in successful implementation of practical training for a social science course during pandemic. Hence, this study can be a preliminary study to assist the decision maker dealing with practical students during pandemic crisis.